Corrigendum: “Overcoming Electrostatic Repulsions During Amyloid Assembly: Effect of Ph and Interaction with Divalent Metals Using Model Peptides” (Arch. Biochem. Biophys. 2017 621 (46–53), s0003986116305355 (10.1016/J.Abb.2017.03.003)) - Diaz-Espinoza, R (Academic Press, 2020)
The authors regret that the information about funding for this article was incomplete and it must state the following updated information: This work was supported by research grants CONICYT PAI/CONCURSO NACIONAL INSERCIÓN EN LA ACADEMIA, CONVOCATORIA 2016 FOLIO PAI79160143, CONICYT/FONDECYT/3150054 and CONICYT/FONDECYT/11160554. The authors would like to apologise for any inconvenience caused. © 2020 Elsevier Inc.